Alterations in GABAA-Receptor Trafficking and Synaptic Dysfunction in Brain Disorders - Mele, Miranda; Costa, Rui O.; Duarte, Carlos B. (Frontiers in Cellular Neuroscience, 2019)
GABAA receptors (GABAAR) are the major players in fast inhibitory neurotransmission in the central nervous system (CNS). Regulation of GABAAR trafficking and the control of their surface expression play important roles in the modulation of the strength of synaptic inhibition. Different pieces of evidence show that alterations in the surface distribution of GABAAR and dysregulation of their turnover impair the activity of inhibitory synapses. A diminished efficacy of inhibitory neurotransmission affects the excitatory/inhibitory balance and is a common feature of various disorders of the CNS characterized by an increased excitability of neuronal networks. The synaptic pool of GABAAR is mainly controlled through regulation of internalization, recycling and lateral diffusion of the receptors. Under physiological condition these mechanisms are finely coordinated to define the strength of GABAergic synapses. In this review, we focus on the alteration in GABAAR trafficking with an impact on the function of inhibitory synapses in various disorders of the CNS. In particular we discuss how similar molecular mechanisms affecting the synaptic distribution of GABAAR and consequently the excitatory/inhibitory balance may be associated with a wide diversity of pathologies of the CNC, from psychiatric disorders to acute alterations leading to neuronal death. A better understanding of the cellular and molecular mechanisms that contribute to the impairment of GABAergic neurotransmission in these disorders, in particular the alterations in GABAAR trafficking and surface distribution, may lead to the identification of new pharmacological targets and to the development of novel therapeutic strategies.